2021
DOI: 10.1186/s12889-021-11153-5
|View full text |Cite
|
Sign up to set email alerts
|

Weight-related behaviors and weight loss maintenance: a cross-sectional study in Cyprus

Abstract: Background This study examined the differences between maintainers and regainers regarding obesity related eating behaviors. A secondary objective was to develop an eating behavior index predicting the likelihood of successful weight loss maintenance. Methods The current cross-sectional evaluation conducted in Cyprus was part of the MedWeight (Greek) study. Eligible for participation were Cypriot (maintainers = 145; regainers = 87) adult men and wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Dining out and fast-food rich diets are often characterised by high-energy density, high-fat, larger food portions, and higher consumption of sugar-sweetened beverages ( 23 ), while home-cooked meals involve healthier food preparation methods and more dietary varieties ( 24 ). Studies in adolescents and adults have demonstrated that increasing the number of meals at home can improve diet quality and reduce obesity and related diseases ( 25 ) due to increased fruit/vegetable and dairy consumption and reduced consumption of sugar-sweetened beverages and unhealthy snacks ( 26 ). Our study found that physicians had more meals outside and fewer meals at home, consistent with the results of previous studies ( 27–29 ), which demonstrated physicians’ high consumption of fast food and alcoholic beverages and less intake of fruits and vegetables.…”
Section: Discussionmentioning
confidence: 99%
“…Dining out and fast-food rich diets are often characterised by high-energy density, high-fat, larger food portions, and higher consumption of sugar-sweetened beverages ( 23 ), while home-cooked meals involve healthier food preparation methods and more dietary varieties ( 24 ). Studies in adolescents and adults have demonstrated that increasing the number of meals at home can improve diet quality and reduce obesity and related diseases ( 25 ) due to increased fruit/vegetable and dairy consumption and reduced consumption of sugar-sweetened beverages and unhealthy snacks ( 26 ). Our study found that physicians had more meals outside and fewer meals at home, consistent with the results of previous studies ( 27–29 ), which demonstrated physicians’ high consumption of fast food and alcoholic beverages and less intake of fruits and vegetables.…”
Section: Discussionmentioning
confidence: 99%
“…It is critical to keep in mind that successful weight maintenance is associated not only with personality traits, but also with other factors such as specific eating behaviors ( 24 ) and behaviors related with physical activity ( 25 ). Our results revealed a higher level of physical activity reported by maintainers compared to regainers.…”
Section: Discussionmentioning
confidence: 99%
“…Data collection took place in public areas with a respond rate of 90%. The data were collected via a face-to-face interview using standardized questionnaires [ 35 , 36 ] and questionnaires used in previous studies which were conducted in Cyprus [ 32 , 37 ]. The questionnaires included questions about participants’ sociodemographic status, medical history, nutritional behaviors (e.g., meal and snack frequency consumption).…”
Section: Methodsmentioning
confidence: 99%